2020
DOI: 10.3390/jfmk6010001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acid Response to Whey Protein Ingestion Following 28 Days of Probiotic (Bacillus subtilis DE111) Supplementation in Active Men and Women

Abstract: We sought to determine if 28 days of probiotic supplementation influenced the plasma amino acid (AA) response to acute whey protein feeding. METHODS: Twenty-two recreationally active men (n = 11; 24.3 ± 3.2 yrs; 89.3 ± 7.2 kg) and women (n = 11; 23.0 ± 2.8 yrs; 70.2 ± 15.2 kg) participated in this double-blind, placebo-controlled, randomized study. Before (PRE) and after 28 days of supplementation (POST), participants reported to the lab following a 10-hr fast and provided a resting blood draw (0 min), then su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
2
Order By: Relevance
“…Additionally, greater maximum concentrations were also found for arginine, serine, ornithine, methionine, glutamic acid, phenylalanine, isoleucine, tyrosine, the sum of the essential amino acids, and the sum of all amino acids when BC30 was added to the milk protein dose. These results contrasted the results found by Townsend et al [16] who conducted a similar study in 22 healthy active men (24.3 ± 3.2 years) that examined the ability of a different bacillus strain, Bacillus subtilis DE111, at a dose of 1 × 10 9 CFU when combined with a 25-g dose of whey protein to impact amino acid appearance. These authors reported no differential responses between leucine, branched-chain amino acid, essential amino acids, and total amino acids and found no difference in area under the curve, highlighting that the benefits of probiotics are strain specific.…”
Section: Introductioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Additionally, greater maximum concentrations were also found for arginine, serine, ornithine, methionine, glutamic acid, phenylalanine, isoleucine, tyrosine, the sum of the essential amino acids, and the sum of all amino acids when BC30 was added to the milk protein dose. These results contrasted the results found by Townsend et al [16] who conducted a similar study in 22 healthy active men (24.3 ± 3.2 years) that examined the ability of a different bacillus strain, Bacillus subtilis DE111, at a dose of 1 × 10 9 CFU when combined with a 25-g dose of whey protein to impact amino acid appearance. These authors reported no differential responses between leucine, branched-chain amino acid, essential amino acids, and total amino acids and found no difference in area under the curve, highlighting that the benefits of probiotics are strain specific.…”
Section: Introductioncontrasting
confidence: 96%
“…In addition to protein source, the age of all recruited cohorts is another important consideration as it pertains to examining the potential impact of co-ingestion a probiotic with a protein source to improve amino acid appearance following digestion. As highlighted throughout, all previous studies [ 6 , 8 , 16 ] utilized cohorts of young participants ranging in average ages of 24–26 years of age. In this respect, “anabolic resistance” is a well-established phenomenon in the skeletal muscle of older adults whereby muscle protein synthesis is diminished in response to both resistance exercise [ 19 ] and protein ingestion [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown DE111 ® to alleviate occasional constipation or diarrhea in healthy adults, while regulating blood lipid levels and suppressing gut and peripheral inflammation (Cuentas et al, 2017;Trotter et al, 2020;Freedman et al, 2021). In adult athletes, DE111 ® consumption reduced circulating TNF-α levels in blood and enhanced body composition in females when combined with post-workout nutrition (Toohey et al, 2020;Townsend et al, 2021). In pediatric cohort (children aged between 2 and 6 years) DE111 ® was well tolerated and was associated with positively modulating the gut microbiome (Paytuví-Gallart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the B. subtilis strain MB40 has been shown to be safe and support GI health in a randomized, double-blind, placebo-controlled trial of 100 healthy adults [ 17 , 35 ]. Additionally, B. inaquosorum DE111 supplementation has been shown to be safe in both adult and pediatric human subjects [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Altogether, these studies provide a large body of clinical evidence that Bacillaceae spp., including B. subtilis , are safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%